Advertising Controversial Products in the Asia Pacific: What Makes Them Offensive? - Fam, Kim Shyan (Journal of business ethics, 2003)
The advertising of controversial products/services and the use of controversial images to "cut through the clutter" in the marketplace appears to be increasing around the world. However, apart from the general ethical issue regarding the deliberate use of controversial/offensive images for public viewing that may offend some people, it is important to determine what makes a controversial advertisement offensive? A questionnaire was distributed to 1014 students across four different countries in the Asia Pacific region to determine what type of products are seen as offensive and the reasons they are offensive. The results present some important implications for international marketers.